2023
DOI: 10.1111/1556-4029.15201
|View full text |Cite
|
Sign up to set email alerts
|

Developing a new scoring method to evaluate human decomposition in a humid, continental (Dfb) climate in Quebec

Abstract: The published literature shows a lack of methods to evaluate the patterns and extent of decomposition of human remains and to estimate the post‐mortem interval (PMI) in humid, continental (Dfb) climates such as Quebec. The aim of this study was to address this gap in the current knowledge base by providing the first observations from human corpses studied under controlled conditions in Quebec. A 12‐month study was conducted at the site for Research in Experimental and Social Thanatology; the first human taphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Future studies can moreover implement clothing or alternate locations to respectively investigate forensically relevant scenarios and to help capture the biogeographic variability of Oahu [ 81 , 111 ]. Managing limitations and identifying avenues for further research will be aided by the incorporation of multivariate statistical analysis and emerging theory [ 22 , 81 , [111] , [112] , [113] ]. The current data have great potential for multivariate analyses and these will be prioritized as a more equal distribution of seasons is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies can moreover implement clothing or alternate locations to respectively investigate forensically relevant scenarios and to help capture the biogeographic variability of Oahu [ 81 , 111 ]. Managing limitations and identifying avenues for further research will be aided by the incorporation of multivariate statistical analysis and emerging theory [ 22 , 81 , [111] , [112] , [113] ]. The current data have great potential for multivariate analyses and these will be prioritized as a more equal distribution of seasons is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The postmortem fate of human remains has been studied by several researchers for the past few decades to better understand how the complex human body decomposes in different scenarios [51][52][53][54][55]. Though there is still much to discover when it comes to human taphonomy, studies have shown that cadavers can display distinct states and patterns of decay even when sharing the same PMI and burial conditions [12,17,56,57].…”
Section: Future Perspectivesmentioning
confidence: 99%